PEMBENTUKAN KELOMPOK WANITA TANI TERNAK KAMBING DAN PELATIHAN MOL UNTUK PENINGKATAN PRODUKTIVITAS DI DESA GUMELAR, BANYUMAS - Amanda, Ariesta; Fitria, Restuti; Pambudi, Mardhika Ardi; Rayhan, Muhammad (Jurnal Abdi Insani, 2025)
Somebody carried out yhis activity to optimize the role of women farmers through the establishment of the Independent Advanced Goat Livestock Farmers Group with MOL training to increase the productivity of farmers in Gumelar Village. This service program is designed through a participatory approach with socialization stages, group management training, technical training on feed processing using MOL starters, and continuous mentoring. The results of the activity show that the formation of the Goat Livestock Farmers Women Group can increase the capacity of members in managing livestock businesses in a more structured manner. Furthermore, the evaluation of activities was measured by pre-test and post-test questionnaires. Group members gain skills in feed processing management using vegetable waste-based MOL Starters. The results of the pre-test showed an average of 42% of farmers' understanding, and after the activity (post-test), increased to an average of 81%. In addition, strengthening group institutions provides space for women farmers to play an active role in decision-making, expand cooperation networks, and access market opportunities. Before the training (pre-test), the average level of technical & managerial skills was 38%. After the training (post-test), the skill level increased to an average of 83%. The real impact that can be seen is the increase in livestock productivity, the efficiency of business management, and the increase in the income of farmer families. Socially, this program also strengthens solidarity among members, increases the confidence of women farmers, and encourages gender equality in the development of agriculture and village livestock. Thus, optimizing the role of women farmers through the formation of livestock groups has proven to be effective as a strategy to empower rural communities to achieve economic independence and better welfare.